FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PELAKSANAAN STANDARD OPERATIONAL PROCEDURE (SOP) PENGEMUDI BUS RAPID TRANSIT (BRT) KORIDOR I SEMARANG - Muhammad Afif Fahrudin; Siswi Jayanti; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2018)
ABSTRACTStandard Operational Procedure (SOP) of BRT driver's is established with the aim for ensuring the comfort and safety both drivers and passengers. Complaints data received by managers shows that there are still many drivers who work not appropriate with procedures. The purpose of this study was to describe and analyze the relationship between working period, knowledge, motivation, attitute, vehicle condition, supervision, reward and punishment with compliance toward SOP on BRT drivers corridor I Semarang. This study uses cross sectional study which is a form of observational study and analytic descriptive. The population of the study was 30 BRT drivers with total sampling method. The instruments of this research were questionnaire (for working period, knowledge, motivation, attitute, vehicle condition, supervision, reward and punishment) with closed answer and observational task critical behaviour checklist (for compliance toward SOP)  Statistical analysis using Rank Spearman correlation test. The result showed that drivers with high compliance is 43.3%, 53.3% respondents with working period ≥ 6 months, 73.3% respondents with high knowledge, 53.3% respondents with good motivation, 66.7 % respondents with good attitude,76.7 % respondents with safe vehicle condition, 86.7 % respondents with good supervision, 63.3% respondents with good reward and punishment. The correlation analysis showed that no correlation between working period (p= 0.694), vehicle condition (p= 0.857), supervision (p=0.194), reward and punishment (p=0.619) with compliance toward SOP. There is correlation between knwoledge (p=0.002) , motivation (p= 0.014), and attitude (p= 0.039) with compliance toward SOP. Managers should evaluate the existing SOP to be more clear. In additon, it is necessary to optimize supervision of drivers, salary feasibility evaluation, and fair rewards and punishment.